Bioactive Coatings on 3D Printed Polycaprolactone Scaffolds for Bone Regeneration: A Novel Murine Femur Defect Model for Examination of the Biomaterial Capacity for Repair - Karen M. Marshall; Jonathan P. Wojciechowski; Vineetha Jayawarna; Abshar Hasan; Cécile Echalier; Sebastien J. P. Callens; Tao Yang; Janos M. Kanczler; Jonathan I. Dawson; Alvaro Mata; Manuel Salmeron‐Sanchez; Molly M. Stevens; et al. (Advanced Materials Interfaces)
Abstract Bone tissue engineering seeks to develop treatment approaches for nonhealing and large bone defects. An ideal biodegradable scaffold will induce and support bone formation. The current study examines bone augmentation in critical‐sized bone defects, using functionalized scaffolds, with the hypothesized potential to induce skeletal cell differentiation. 3D printed, porous poly(caprolactone) trimethacrylate (PCL‐TMA900) scaffolds are applied within a murine femur defect, stabilized by a polyimide intramedullary (IM) pin. The PCL‐TMA900 scaffolds are coated with i) elastin‐like polypeptide (ELP), ii) poly(ethyl acrylate) (PEA)/fibronectin (FN)/bone morphogenetic protein‐2 (PEA/FN/BMP‐2), iii) both ELP and PEA/FN/BMP‐2, or iv) Laponite nanoclay binding BMP‐2. Sequential microcomputed tomography (µCT) and histological analysis are performed. PCL‐TMA900 is robust and biocompatible and when coated with the nanoclay material Laponite and BMP‐2 induce consistent, significant bone formation compared to the uncoated PCL‐TMA900 scaffold. Critically, the BMP‐2 is retained, due to the Laponite, producing bone around the scaffold in the desired shape and volume, compared to bone formation observed with the positive control (collagen sponge/BMP‐2). The ELP and/or PEA/FN/BMP‐2 scaffolds do not demonstrate significant or consistent bone formation. In summary, Laponite/BMP‐2 coated PCL‐TMA900 scaffolds offer a biodegradable, osteogenic construct for bone augmentation with potential for development into a large scale polymer scaffold for clinical translation.